Detection of Nitric Oxide from Chickpea Using DAF Fluorescence and Chemiluminescence Methods. Issue 4 (20th April 2022) - Kumari, Aprajita; Bhatoee, Manbir; Singh, Pooja; Kaladhar, Vemula Chandra; Yadav, Nidhi; Paul, Debarati; Loake, Gary J.; Gupta, Kapuganti Jagadis
Abstract: The free radical nitric oxide (NO) has emerged as an important signal molecule in plants, due to its involvement in various plant growth, development, and stress responses. For elucidating the role of NO, it is very important to precisely determine, localize, and quantify NO levels. Due to a relatively short half‐life and its rapid, complex reactivity with other radicals, together with its capacity to diffuse from the source of production, the quantification of NO in whole plants, tissues, organelles, and extracts is notoriously difficult. Hence, it is essential to employ sensitive procedures for precise detection of NO. Currently available methods can fulfill many requirements to precisely determine NO, but each method has several advantages and pitfalls. In this article, we describe a detailed procedure for the measurement of NO by diaminofluorescein (DAF) in cell‐permeable forms (DAF‐FM‐DA). In this method, the tissues are immersed in DAF‐FM DA, leading to their diffusion from the plasma membrane to the inside of the cell, where intracellular esterases cleave the ester bonds, leading to DAF‐FM release. The resulting DAF‐FM reacts with intracellularly generated NO and forms highly fluorescent triazolofluorescein (DAF‐FMT), which can be localized and monitored by fluorescence or confocal microscopy, and can also be detected via fluorimetry and flow cytometry. DAF dyes are very popular as they are non‐invasive, relatively easy to handle, and commercially available. Another precise and very sensitive method is chemiluminescence detection of NO, where NO reacts with ozone (O3 ), leading to emission of a quantum of light from which NO can be calculated. Using chickpea seedlings, we describe in detail the measurement of NO using DAF‐FM‐DA and chemiluminescence methods. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Measurement of nitric oxide from chickpea seedlings using DAF‐FM DA fluorescence with fluorescence and confocal microscopy Basic Protocol 2 : Chemiluminescence detection of nitric oxide from chickpea seedlings